PENGARUH PENGGUNAAN SMARTPHONE TEHADAP POLA KOMUNIKASI INTERPESONAL SISWA SMP NEGERI 50 BANDUNG - Pitthauly Haomasan; Nofharina Nofharina (Jurnal Komunikasi, 2018)
ABSTRACTNowadays smartphones can be consumed from young to old age. Motives teenagers in using the smartphone quite diverse, namely, the sophistication of features, fast internet access, ease of access to social media, entertainment facilities and help in doing homework. In early January 2017, SMP Negeri 50 Bandung set a ban on bringing smartphones to school, due to the recent years the influence of smartphone making problems in school. This study was conducted to find out how much the influence of using smartphones to interpersonal communication patterns of students of SMP Negeri 50 Bandung. This research is associated with Uses and Gratification theory and the method is quantitative with the type of descriptive research. This study involved one independent variable and one dependent variable. Using probability sampling method with Slovin approach with the number of respondents 82 people. Data analysis techniques used are descriptive and multiple linear regression analysis. Based on the results of simultaneous hypothesis testing, a significant influence on the use of smartphones against interpesonal communication patterns. This is evidenced by the value of F-count(41.644) lebih dari F-table (2.722) with a significance level of 5%. The result of coefficient of determination showed that Frequency of Use, the Variety of Content and Activity give influence of 61,6% to Interpersonal Communication Pattern of students of SMP Negeri 50 Bandung. While the action of 38.4% is the contribution of other variables that are not examined in this study. Can be concluded that SMP Negeri 50 Bandung prohibits bringing smartphones to school so obtained despite the prohibition of bringing the smartphone in effect to make high interpersonal communication patterns of students of SMP Negeri 50 Bandung.